12th Annual IEEE Symposium on Field-Programmable Custom Computing Machines
DOI: 10.1109/fccm.2004.33
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Acceleration of Rigid Molecule Interactions

Abstract: Abstract. Modeling of molecule interactions often uses two or more successive models of increasing complexity. Rigid models based on correlation techniques are common as early screening passes-to detect interactions worth costlier examination-and are often at the heart of later passes as well. Even these rigid models are time-consuming when applied to large models at 10 3 − 10 5 different three-axis rotations. This paper presents an FPGA structure for performing the correlations efficiently by using a systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…As each evaluation can take many CPU-hours, huge processing capability must be applied. Docking codes have been accelerated with FPGAs [15, 18, 20, 21], Cell [14], and GPUs [13, 17, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…As each evaluation can take many CPU-hours, huge processing capability must be applied. Docking codes have been accelerated with FPGAs [15, 18, 20, 21], Cell [14], and GPUs [13, 17, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Our GPU work accelerates the PIPER docking code [5]; we summarise this below and compare it with the FPGA approach presented here. The present authors and collaborators have also previously used FPGAs to demonstrate proof-of-concept FPGA-based acceleration of ZDOCK and some other systems [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [6, 7] we showed that, for FPGA-based coprocessors, the original direct correlation – rather than an FFT – is sometimes the preferred method for computing rigid molecule docking. Two reasons for this are the inherent efficiency with which FPGAs perform convolutions and the modest precision (2–7 bits) of the original voxel data.…”
Section: Introductionmentioning
confidence: 99%
“…This implementation is described in references [21,22]. The applied algorithm uses 3D correlation which is a common rigid-body docking technique.…”
Section: Docking With 3d Correlationmentioning
confidence: 99%
“…In order to exploit this the implementation has a flexible structure; the design can be easily configured to adapt different scoring schemes. The initial implementation [21] used a very simple voxel type consisting of only two bits that distinguish molecule interiors from exteriors and mark the surface of the molecules. The final version allows using voxels with tuple data type that represent different effects including directional interactions like hydrogen bonding.…”
Section: Docking With 3d Correlationmentioning
confidence: 99%